Midwives' Support and the Success of Early Breastfeeding Initiation among Postpartum Mothers - Sri Ilawati; Herviza Wulandari Pane; Shinta Audina Pratiwi (Benih : Journal of Midwifery, 2026)
Background: Early Breastfeeding Initiation (EBI) is a WHO/UNICEF global strategy to reduce neonatal mortality. However, its implementation still faces challenges, including the role of midwives as facilitators. Methods: A descriptive qualitative study using a case-study approach. Data were collected through semi-structured interviews and observation of 5 midwives/nurses in the Lactation Room of USM Hospital Kelantan. Data were analyzed using data reduction, data display, and verification. Results: (1) Midwives' support included education (benefits and technique of EBI), direct assistance, and promotion of rooming-in (100% of mothers); (2) EBI success was achieved in 80% of mothers, with infants finding the nipple within 1 hour (80%), skin-to-skin contact ≤2 hours (100%), and strengthened emotional bonding (100%); (3) There was a clear relationship between midwives' support and EBI success: mothers with high support (4 individuals) achieved optimal EBI, while limited support (1 individual) resulted in partial EBI. Conclusion: Holistic midwifery support (education, technical assistance, and emotional support) plays a crucial role in EBI success. Strengthening midwives' capacity through continuous training is recommended to optimize the program.